OP0050 Gene polymorphisms of the glucocorticoid receptor and 11Β-hydroxysteroid dehydrogenase type 1 affect relevant clinical outcomes in anca associated vasculitis. (12th June 2018) - Hessels, A.C.; Tuin, J.; Sanders, J.S.F.; Huitema, M.G.; van Rossum, E.F.C.; Koper, F.J.W.; van Beek, A.P.; Stegeman, C.A.; Rutgers, A.
Abstract : Background: High doses of exogenous glucocorticoids (e.g., prednisolone) are a standard part of treatment for ANCA-associated vasculitis. 1 Efficacy and toxicity of glucocorticoid treatment differ widely between individuals. 2 We hypothesised that this can be partly explained by genetic polymorphisms of the glucocorticoid receptor (GR) and 11β-hydroxysteroid dehydrogenase type 1 (HSD11B1) that influence glucocorticoid sensitivity. Objectives: To investigate whether five haplotypes of the Glucocorticoid Receptor gene (NR3C1) and a single nucleotide polymorphism of 11β-hydroxysteroid dehydrogenase type 1 (HSD11B1) are associated with treatment efficacy and toxicity in ANCA associated vasculitis. Methods: A total of 241 ANCA associated vasculitis patients were genotyped for five polymorphisms of the glucocorticoid receptor gene and one polymorphism of the HSD11B1 gene. Glucocorticoid receptor gene haplotypes were predicted based on genotyping results. Relapse free survival, mortality, renal survival, metabolic adverse events and infections were compared between carriers and non-carriers of glucocorticoid receptor haplotypes and the HSD11B1 genotype. Results: Carriers of the ER22/23EK haplotype of the glucocorticoid receptor had a significantly higher risk of 10 year mortality (Hazard Ratio (HR) 3.0, 95% confidence interval, CI: 1.2 to 7.3), more frequently required plasmapheresis treatment (p=0.04) and had a higher risk of developing end-stage renal disease (HR 7.4, 95% CI: 1.9 to 28.7). Carriers of a minor variant of HSD11B1 more frequently experienced relapse (HR 2.5, 95% CI: 1.5 to 4.1), except if they also carried the Bcl I haplotype of the glucocorticoid receptor. Homozygous carriers of the Bcl I haplotype had a higher risk of developing hypertension (HR 2.7, 95% CI: 1.2 to 5.7) and dyslipidemia (HR 4.1, 95% CI: 1.8 to 9.6). Occurrence of infections neither differed between GR haplotypes, nor between HSD11B1 genotypes. Conclusions: The ER22/23EK and Bcl I haplotype of the glucocorticoid receptor and a polymorphism of the gene for HSD11B1 are associated with clinically relevant inflammatory and metabolic outcomes in ANCA associated vasculitis. References: [1] Yates M, Watts RA, Bajema IM, Cid MC, Crestani B, Hauser T, et al. EULAR/ERA-EDTA recommendations for the management of ANCA-associated vasculitis. Ann Rheum Dis2016Sep;75(9):1583–1594. [2] Quax RA, Manenschijn L, Koper JW, Hazes JM, Lamberts SW, van Rossum EF, et al. Glucocorticoid sensitivity in health and disease. Nat Rev Endocrinol2013Nov;9(11):670–686. Disclosure of Interest: None declared